Living Sunnah Tradisi Pembacaan Manaqib di Pondok Pesantren Darul Qur’an Sumbersari Kediri - Siti Rochmah; Abd Majid Abror (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Manaqib is a story of the mercy of the guardians, by reading the story of the sholeh people, such as the story of the Prophet or Auliya' (lovers of God) aims to exemplify their commendable morals by using very beautiful language, as for the emergence of manaqib in Indonesia is closely related to the history of the spread of Sufism in Indonesia. The tradition of reading manaqib night eleven hijri is carried out in mushola and in serambi down /first floor pondok pesansantren Darul Qur'an at 22.00 until completion, followed by all students and led by one of the ustadzah Pondok, practice manaqib by KH. Abi Musa al-'Asy'ari and only diploma once every three years during Ramadan so that students who want to follow it must be romadhonan ordered trend. The spiritual experience of Pondok Pesantren Darul Qur'an students while attending the study of Sheikh Abdul Qadir Al-jilani's manaqib is very diverse. Some feel like the heart is becoming calmer, more peaceful, feel more eager to study, study and also be diligent in living the charities of Sunnah.